Variation, Indispensability, and Masking in the M protein. Issue 2 (February 2018) - Ghosh, Partho
Abstract : The M protein is the major surface-associated virulence factor of group A Streptococcus (GAS) and an antigenically variable target of host immunity. How selection pressures to escape immune recognition, maintain indispensable functions, and mask vulnerabilities have shaped the sequences of the >220 M protein types is unclear. Recent experiments have shed light on this question by showing that, hidden within the antigenic variability of many M protein types, are sequence patterns conserved for recruiting human C4b-binding protein (C4BP). Other host factors may be recruited in a similar manner by conserved but hidden sequence patterns in the M protein. The identification of such patterns may be applicable to the development of a GAS vaccine. Trends: Recruitment of C4BP by multiple M types occurs through conserved sequence patterns that are hidden within M protein variability. Phylogenetic analysis offers a way to group the M protein into two broad clades, and clusters within those clades. Like C4BP, factor H (FH) is recruited by M protein variable sequences, but the number of M types that bind FH is unclear, as are the sequence patterns underlying the recruitment. The M1 protein variable region detoxifies the antimicrobial peptide LL-37 through a 'protein trap.' The M1 protein variable region similarly detoxifies the antibacterial activity of histones. Instability and conformational dynamics in the M1 B-repeats are required for recruitment of fibrinogen. The M1 B-repeats have a multiplicity of functions, including binding glycans belonging to blood group antigens and triggering pyroptosis in macrophages.